2019
DOI: 10.7241/ourd.20184.1
|View full text |Cite
|
Sign up to set email alerts
|

Scabious erythroderma – a rare clinical variant of scabies

Abstract: Background: Erythroderma (exfoliative dermatitis) is an emergency condition in dermatology in which not less than 90% of skin surface is affected. The presenting features are erythema, skin scaling and itching, fever and lymphadenopathy. The most common cause of erythroderma is a preexisting dermatosis (psoriasis, atopic dermatitis, eczema, seborheic dermatitis, lichen rubra pilaris, lichen planus, pemphigus foliaceous), drug reactions, lymphoma, leukemia and visceral neoplasias. Erythroderma is a diagnostical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
0
0
1
Order By: Relevance
“…Одним из основных клинических критериев НЧ является эритродермия. Если при генерализованной эритродермии паразитарного происхождения отсутствуют корки, то эта форма заболевания называется скабиозной эритродермией [29].…”
Section: Discussionunclassified
“…Одним из основных клинических критериев НЧ является эритродермия. Если при генерализованной эритродермии паразитарного происхождения отсутствуют корки, то эта форма заболевания называется скабиозной эритродермией [29].…”
Section: Discussionunclassified
“…Many drugs are implicated as a cause of erythroderma, which include: sulphonamides, penicillin, isoniazid, antimalarial, allopurinol, phenytoin, omeprazole, captopril, vancomycin, infliximab, streptomycin, PAS, pyrazinamide, ethambutol, and rifampicin [5][6][7][8][9]. Scabies also implicated as a cause of erythroderma [10][11][12]. Jose et al [12], in an epidemiological study on erythroderma in India found that psoriasis is the common cause of erythroderma (38.23%), followed by the drug induced (20.59%), while atopic dermatitis, irritant dermatitis, pityriasis rubra pilaris, scabies, congenital ichthyosiform, pemphigus foliaceous, systemic lupus erythematosus and T. corporis form 5.88% for each.…”
mentioning
confidence: 99%